Perancangan Sistem Manajemen Data Produksi Batu Bara Di PT Mitra Terminal Kaltim - Jahra Sofie Azizah; Zahra Aqika Saputri (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This dedication aims to design a Coal Production Data Management System at PT. Mitra Terminal Kaltim using the Waterfall method to enhance efficiency. Coal production data, including hauling, crushing, barging, coal getting, stock reporting, and daily reporting, is currently manually managed using Excel, resulting in process inefficiencies. Through systematic design steps, this dedication emphasizes the User Interface (UI) to expedite and streamline the production data processing. The expected outcome is to support coal production monitoring more swiftly and efficiently.